Mirabegron: first β3 agonist in treatment of overactive bladder - Gill, Paramdeep Singh; Grewal, Nipunjot (International Journal of Basic & Clinical Pharmacology, 2017)
Mirabegron is the first and only β3 agonist approved by US FDA in June 2012 for treatment of Overactive bladder with symptoms of urge incontinence, urgency and urinary frequency. It is the first oral OAB treatment with a distinct mechanism of action since the launch of anticholinergic agents 30 years ago. It causes relaxation of detrusor smooth muscle by its agonist action at β3 receptors leading to increased storage capacity of bladder. It has been studied extensively in more than 10,000 individuals over 10 years.